Social dimension and participation in vocational education and training : proceedings of the 2nd conference "Crossing Boundaries in VET" - Kaiser, Franz [Herausgeber]; Krugmann, Susann [Herausgeber] (Universität Rostock, 2017)
"One year after founding the Institute for VET at the University of Rostock and two years after the first "Crossing boundaries in Vocational Education and Training - Conference" in Bremen the conference with focus on social dimension and participation took place in August 2017 in Rostock. We invited researchers from the field of vocational education and training as well as from adjacent disciplines to participate and contribute presentations for the conference with respect to the following reference levels. The publication introduces 44 research papers from 17 countries which have been presented on the International VET-Conference Crossing Boundaries in Vocational Education and Training: Social Dimension and Participation in Rostock." Following sessions are presented in this proceedings: Communication and conflicts; CBET and qualification framework and their impact; Teacher Training; Transfer; Curricular Design; Permeability - recognition of competencies; Transfer; Innovation projects and the role of research; Industry 4.0; Learning process in school and workplace; Integration of Youth; Teacher Training; Work orientation in higher Education; Cooperation of learning venue. (BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; P 3.2 Lehrpersonal; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; L 2.1.3 Erfahrungslernen; P 1.1 Jugendliche; Industrie 4.0; Bildungspersonal; Ausbildung der Ausbilder; Bildungstransfer; Durchlässigkeit im Bildungssystem; Soziale Integration; Benachteiligter Jugendlicher; Lernen am Arbeitsplatz; Curriculumentwicklung; Beziehung Bildungssystem Beschäftigungssystem; Schweiz; Spanien; Großbritannien; Litauen; Estland; Rumänien; Ägypten; Indonesien; Peru; Australien; China